2018
DOI: 10.1590/1807-1929/agriambi.v22n3p212-217
|View full text |Cite
|
Sign up to set email alerts
|

Performance of onion cultivars as a function of spacing between plants

Abstract: The objective of this study was to evaluate the performance of onion cultivars as a function of the spacing between plants. The experimental design was a complete randomized block in a 3 x 4 factorial scheme, with four replicates. The treatments were composed of the combination between three onion cultivars (Vale Ouro IPA 11, Serena and Rio das Antas) and four plant spacings (3, 6, 8 and 10 cm). The evaluated characteristics were total, marketable and unmarketable yield of bulbs, percentages of bulbs in classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
1
5
1
Order By: Relevance
“…The values observed were lower than those found by Santos et al (2018), who evaluated the performance of onion cultivars as a function of plant spacing and observed that cultivar 'IPA 11' was more pungent than 'Rio das Antas', with PUNG values ranging from 6.06 to 6.92 and 4.85 to 5.67 μmol g -1 , respectively. Grangeiro et al (2008), evaluating the qualitative characteristics of onion genotypes in Mossoró/RN, also recorded a higher PUNG value for cultivar 'IPA 11' (7.60 μmol g -1 ) compared with that found in the present study.…”
Section: Resultscontrasting
confidence: 71%
“…The values observed were lower than those found by Santos et al (2018), who evaluated the performance of onion cultivars as a function of plant spacing and observed that cultivar 'IPA 11' was more pungent than 'Rio das Antas', with PUNG values ranging from 6.06 to 6.92 and 4.85 to 5.67 μmol g -1 , respectively. Grangeiro et al (2008), evaluating the qualitative characteristics of onion genotypes in Mossoró/RN, also recorded a higher PUNG value for cultivar 'IPA 11' (7.60 μmol g -1 ) compared with that found in the present study.…”
Section: Resultscontrasting
confidence: 71%
“…This satisfactory yield achieved is due to the technologies applied along the study, such as the use of adapted cultivars, no-tillage, dense cultivation, weekly split fertilization applied via irrigation water and other cultural practices performed judiciously, whenever necessary. Santos et al (2018) found similar results, applying 150 kg ha -1 of P 2 O 5 , for the same cultivars and spacing with TY of 86.52, 96.52, 94.95 t ha -1 and MY of 84.55, 95.55, 94.58 t ha -1 for the cultivars IPA11, Rio das Antas and Serena, respectively, in soil with a high P( mehlich extractor ) content. The yields were also higher than those found by Costa et al (2008) for the cultivar Alfa Tropical (13.2 t ha -1 ) and by Silva (2015) for the cultivars Red Creole (14.23 t ha -1 ), Baia Periforme (21.90 t : - Rev.…”
Section: Resultssupporting
confidence: 65%
“…In addition to the selection of the cultivar, the sowing time appropriate to the climate and environment of the production area are essential factors for obtaining satisfactory yields (Ikeda, Kinoshita, Yamamoto, & Yamasaki, 2019). A stable environment, with low temperature and humidity variation, absence of heavy rain, low incidence of pests and diseases, as well as the use of appropriate technologies for irrigation, fertigation, sowing and density (Santos et al, 2018), also contribute to good plant development and increased productivity in onion cultivation.…”
Section: Introductionmentioning
confidence: 99%